A case report of preoperative care of management protocol for craniotomy after digital subtraction angiography (DSA) - Susanto, Dibyo Harjo; Kariasa, I Made (Holistik Jurnal Kesehatan, 2024)
Background: A brain tumor is an unnatural or abnormal mass growth of brain tissue that develops uncontrollably. Petroclival meningioma represents a serious challenge in neurosurgical cases. Surgical procedures or tumor removal via craniotomy have a significant risk of the patient's post-operative condition which will affect the patient's quality of life in the future, so holistic and comprehensive nursing care is needed. Purpose: To analyze cases of brain tumors in patients with petroclival meningioma after digital subtraction angiography (DSA) was performed in preparation for tumor removal via craniotomy. Method: Case study involving respondents through a nursing care analysis approach using the Roy adaptation model. The patient was a 51-year-old woman who underwent a digital subtraction angiography (DSA) procedure in preparation for surgical craniotomy to remove the tumor. Results: The main needs found from the nursing assessment process were sensation (chronic pain), neurological (risk of ineffective perfusion of brain tissue), activity or mobility (barriers to physical mobility), protection (risk of injury or falls), and personal. protection. concept (anxiety). Providing appropriate nursing care can help patients prepare for surgery, speed up the post-operative recovery process, and help patients adapt to post-operative conditions with the aim of shortening the treatment period and improving the quality of life of post-operative patients. Conclusion: Nursing care using the Roy adaptation model approach is quite useful in handling petroclival meningioma cases because it focuses on the patient's ability to adapt to the condition of the disease. Suggestion: Future researchers need to apply nursing care using the Roy adaptation model approach which is supported by the development of nursing interventions for petroclival meningioma patients through the application of evidence based nursing (EBN), so that it will further improve the quality of nursing services.   Keywords: Roy Adaptation; Nursing care; Petroclival Meningioma; Craniotomy.   Pendahuluan: Tumor otak merupakan pertumbuhan massa jaringan otak yang tidak wajar atau abnormal dan berkembang secara tidak terkontrol. Meningioma petroclival menjadi salah satu tantangan berat pada kasus bedah saraf. Tindakan pembedahan atau craniotomy removal tumor memiliki risiko yang cukup besar terhadap kondisi pasien pasca tindakan pembedahan yang akan memengaruhi kualitas hidup pasien ke depannya, sehingga diperlukan asuhan keperawatan yang holistik dan komprehensif.   Tujuan: Untuk menganalisis kasus tumor otak pada pasien meningioma petroclival pasca tindakan digital subtraction angiography (DSA) dalam persiapan craniotomy removal tumor. Metode: Studi kasus yang melibatkan seorang responden melalui pendekatan analisis asuhan keperawatan menggunakan model adaptasi Roy. Pasien berjenis kelamin perempuan berusia 51 tahun pasca tindakan digital subtraction angiography (DSA) untuk persiapan operasi craniotomy removal tumor. Hasil: Kebutuhan utama yang ditemukan dari proses pengkajian keperawatan adalah sensasi (nyeri kronik), neurologis (risiko ketidakefektifan perfusi jaringan serebral), aktivitas atau mobilitas (hambatan mobilitas fisik), perlindungan (risiko cedera atau jatuh), dan konsep diri (ansietas). Pemberian asuhan keperawatan yang tepat dapat membantu pasien mempersiapkan dalam menghadapi tindakan operasi atau pembedahan, mempercepat proses pemulihan pasca pembedahan, dan membantu proses adaptasi pasien terhadap kondisi pasca pembedahan dengan tujuan dapat mempersingkat masa perawatan dan meningkatkan kualitas hidup pasien pasca tindakan pembedahan. Simpulan: Asuhan keperawatan dengan pendekatan model adaptasi Roy cukup bermanfaat dalam penanganan kasus meningioma petroclival karena berfokus pada kemampuan pasien untuk beradaptasi terhadap kondisi penyakitnya. Saran: Bagi peneliti selanjutnya, perlu adanya penerapan asuhan keperawatan dengan pendekatan model adaptasi Roy yang didukung dengan pengembangan intervensi keperawatan pada pasien meningioma petroclival melalui penerapan evidence based nursing (EBN), sehingga akan semakin meningkatkan kualitas asuhan keperawatan.   Kata Kunci: Adaptasi Roy; Asuhan Keperawatan; Meningioma Petroclival; Kraniotomi.